Evaluation of Cyclic Fatigue Resistance of Novel Replica-Like Instruments in Static Test Model - Uğur Aydın; Melih Özdemir; Emre Çulha; Muazzez Naz Baştürk Özer; Bilal Turan (Applied Bionics and Biomechanics)
Introduction. The aim of our study is to comparatively analyze the canal cyclic fatigue resistance of widely used rotary file systems, including EndoArt Touch Gold (ETG), Perfect MTF Plus Gold (PPG), Fanta V-Taper Gold (FVG), and ProTaper Next (PTN). Methods. Stainless steel canals with a 60° angle and a 3-mm curvature radius were specially prepared. The canals were shaped with each rotary file system and tested for resistance using a cyclic fatigue testing apparatus. The number of fracture cycles (NFC; K file tip separation) was measured. Data were analysed by one-way ANOVA and post hoc LSD tests. Results. PTN and PPG rotary file systems exhibited the highest NFC. The NFC value for PTN was 589 ± 63, and for PPG, it was 507 ± 51. Conclusion. The results of this study demonstrate that rotary file systems such as PTN and PPG exhibit higher cyclic fatigue resistance. ETG and FVG rotary file systems also possess generally acceptable cyclic fatigue resistance levels.